(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article explores the role of motivation in the process of military professional training and its impact on training effectiveness. Motivation is a decisive factor for service members in mastering combat and professional skills, maintaining psychological resilience, and enhancing discipline. The study analyzes intrinsic and extrinsic types of motivation, their interrelationship, and modern incentive strategies used in military educational institutions-such as clear goal-setting, individualized approaches, cultivating a competitive environment, employing technological tools, and implementing reflection and feedback mechanisms. The article also substantiates the importance of commanders’ and instructors’ communication skills, socio-psychological support systems, and unit esprit de corps in creating an effective motivational climate. Ultimately, the recommended strategies are shown to improve the quality of military-professional training, strengthen cadets’ learning motivation, and help them achieve high performance in their future careers.